Enhancer of zeste homolog 1/2 dual inhibitor valemetostat outperforms enhancer of zeste homolog 2-selective inhibitors in reactivating latent HIV-1 reservoirs ex vivo - Sedohara, Ayako; Koibuchi, Tomohiko; Yamagishi, Makoto; Koga, Michiko; Arizono, Kotaro; Ikeuchi, Kazuhiko; Kikuchi, Tadashi; Saito, Makoto; Adachi, Eisuke; Tsutsumi, Takeya; Honma, Daisuke; Araki, Kazushi; et al. (Frontiers in Microbiology, 2025)
For the eradication of human immunodeficiency virus type 1 (HIV-1) provirus from people living with HIV-1, reactivation of latently HIV-1-infected cells is essential. Although several latency reversing agents have been identified, eradication of HIV-infected cells has been a challenge. Here, we investigated whether the novel enhancer of zeste homolog 1/2 (EZH1/2) dual inhibitor valemetostat/DS-3201/(R)-OR-S2 could efficiently reactivate latently HIV-1-infected cells in vitro and ex vivo. People living with HIV-1 who were on suppressive combined antiretroviral therapy and with plasma HIV-1 virus levels consistently below 50 copies/mL were enrolled in this study. ACH2 cells were treated with valemetostat for 7–14 days and with suberoylanilide hydroxamic acid (SAHA). CD4+ T cells were treated with valemetostat or the EZH2-selective inhibitors GSK126 and E7438 for 22 days alone or in combination with SAHA. HIV-1 expression in CD4+ T cells was determined. Valemetostat more effectively induced HIV-1 mRNA expression in ACH-2 cells when administered for 14 days than when administered for 7 days. Valemetostat reversed latently HIV-l-infected CD4+ T cells isolated from patients with HIV-1 and induced HIV-1 mRNA expression more potently than GSK126 and E7438. In addition, valemetostat induced HIV-1 mRNA expression more strongly when used in combination with SAHA compared with GSK126 and E7438. Expression levels of 21 hub genes were markedly increased after treatment with valemetostat. Gene Ontology analysis revealed that proteins encoded by these 21 genes were localized to the cell membrane and involved in the immune response. Kyoto Encyclopedia of Genes and Genomes enrichment pathway analysis showed that these 21 hub genes contributed to various signaling pathways, including the JAK–STAT signaling pathway. This study provides novel insights for the development of treatments to reactivate latently HIV-1-infected cells.